The Effects of Human Resource Management Practices on Productivity: A Study of Steel Finishing Lines - Ichniowski, Casey; Kathryn, Shaw; Prennushi, Giovanna (American Economic Review, 1997)
The authors investigate the productivity effects of innovative employment practices using data from a sample of thirty-six homogeneous steel production lines owned by seventeen companies. The productivity regressions demonstrate that lines using a set of innovative work practices, which include incentive pay, teams, flexible job assignments, employment security, and training, achieve substantially higher levels of productivity than do lines with the more traditional approach, which includes narrow job definitions, strict work rules, and hourly pay with close supervision. Their results are consistent with recent theoretical models which stress the importance of complementarities among work practices. Copyright 1997 by American Economic Association.